The House With Sixty Closets: A Christmas Story for Young Folks and Old Children - Child, Frank Samuel, 1854-1922; Brown, J. Randolph (Salt Lake City, UT : Project Gutenberg, 2013)
"The House With Sixty Closets: A Christmas Story for Young Folks and Old" by Frank Samuel Child is a fictional narrative written in the late 19th century. This charming holiday tale centers around a unique house built by a Judge that features an extraordinary number of closets, which play a significant role in the unfolding story. The main characters include the kind Judge, his wife, and a lively band of children who inhabit the house and discover its many secrets during the festive season. At the start of the story, we learn about the illustrious Judge and his wife, who, influenced by their generous natures, designed a home filled with an impressive sixty closets to accommodate their charitable tendencies. When a minister's family moves into the Judge's old parsonage, the children of that household are enchanted by their new home$1 (Bs history and the curious closets. On Christmas Eve, excitement mounts as the children prepare for festivities, sparking whimsical interactions with the ghosts of the Judge and his wife, who come to life from their portraits. This playful introduction sets the stage for a heartwarming exploration of generosity, family, and the magic of Christmas. (This is an automatically generated summary.)s
Release date is 2013-06-16
E-text prepared by David Edwards, Emmy, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Fantasy literature; Christian life -- Juvenile fiction; Christmas stories; Animals -- Juvenile fiction; Conduct of life -- Juvenile fiction; Adventure stories; Friendship -- Juvenile fiction; Siblings -- Juvenile fiction; Kindness -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Cousins -- Juvenile fiction; Christmas -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Children -- Juvenile fiction; Charity -- Juvenile fiction; Generosity -- Juvenile fiction; Imagination -- Juvenile fiction; Empathy -- Juvenile fiction; Husband and wife -- Juvenile fiction; Sharing -- Juvenile fiction; House construction -- Specifications -- Juvenile fiction; Judges -- Juvenile fiction; Linen closets -- Juvenile fiction; Patronage, Ecclesiastical -- Juvenile fiction; Planning -- Juvenile fiction